The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1051/e3sconf/202130403011
|View full text |Cite
|
Sign up to set email alerts
|

Study on machine for processing and preparing the soil for sowing potatoes on ridges

Abstract: The technologies used to prepare the soil for sowing potatoes on ridges, consisting of numerous soil preparation operations, lead to loss of moisture, prolonging the sowing period and increasing operating costs. The aim of the research is to develop a machine for processing and preparing the soil for sowing potatoes on ridges. The authors have developed a technology for preparing fields for sowing potatoes on ridges and a machine for its implementation. The basic principles and methods of classical mechanics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Based on the analysis of the conducted research work, the use of slope field processing and grain sowing technologies and technical tools in developed countries, as well as the requirements of agrotechnical for grain planting, a combined machine for processing and sowing grain on sloped Fields was developed [3,4,7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis of the conducted research work, the use of slope field processing and grain sowing technologies and technical tools in developed countries, as well as the requirements of agrotechnical for grain planting, a combined machine for processing and sowing grain on sloped Fields was developed [3,4,7].…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of research has shown that prevention of water erosion during seeding of grain crops on sloping fields and conservation of moisture in the soil, as well as reduction of fuel, labor, and material costs, can be achieved by applying technologies of soil treatment with simultaneous seeding of grain seeds and formation of anti-water erosion ridges and machines for its implementation [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Uzbekistan is one of the leading countries in the world in the production of melon products and especially valuable varieties of melons, which are famous for their taste qualities not only in our country but also far beyond its borders [1][2][3][4]. Therefore, it is necessary to increase the production volume of melons.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lot of data in the literature regarding the fact that it is most rational to apply organic fertilizers for melon crops locally, which accelerates the formation of the root system, reduces the negative effect of the diversity of natural soil fertility, promotes the alignment of plant development, simultaneous and earlier fruit ripening, increases by 10-30% yield, by 1.0-1.5% sugar content in fruits and others [1][2]. However, this method is practically not used in production due to the lack of tools for the local application of organic fertilizers for melon crops.…”
Section: Introductionmentioning
confidence: 99%
“…To do this, it is necessary that when the soil interacts with the elements of the slitter, its vertical movement prevails. The well-known works, D. Chuyanov [1][2], F. Mamatov , B. Mirzaev [4-7, 12-19, 21, 23, 26], K. Ravshanov [9,22,25,28,33], U. Kodirov [1,21,28,33], I. Temirov [9,11,33], on substantiating the parameters of plow hulls, are mainly aimed at studying the process of lifting and complete rotation of the formation, in which horizontal soil movement prevails. Studies of moving the soil along the oblique blade have been carried out.…”
Section: Introductionmentioning
confidence: 99%